2015
DOI: 10.1371/journal.pone.0126306
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Sugarcane Roots in Response to Low Potassium Stress

Abstract: Sugarcane is the most important crop for supplying sugar. Due to its high biomass, sugarcane needs to absorb a large amount of potassium (K) throughout its lifecycle. In South China, a deficiency of K available in soil restricts the production of sugarcane. Increasing the tolerance of sugarcane to low-K will be an effective approach for improving survival of the crop in this area. However, there is little information regarding the mechanism of tolerance to low-K stress in sugarcane. In this study, a customized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…1). Transcriptional analysis of plants facing short-term and extreme K + deprivation revealed an increase in the expression of K + transporters and channels from the HAK, HKT, and AKT families (Armengaud , 2004;Ma et al, 2012;Shankar et al, 2013;Ruan et al, 2015;Zeng et al, 2015). In our study, we analyzed the impact of long-term K + deprivation in the model legume M. truncatula.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…1). Transcriptional analysis of plants facing short-term and extreme K + deprivation revealed an increase in the expression of K + transporters and channels from the HAK, HKT, and AKT families (Armengaud , 2004;Ma et al, 2012;Shankar et al, 2013;Ruan et al, 2015;Zeng et al, 2015). In our study, we analyzed the impact of long-term K + deprivation in the model legume M. truncatula.…”
mentioning
confidence: 98%
“…However, most studies have only investigated the short-term molecular plant responses to K + deprivation, and not in the context of AM symbiosis. The transcriptional responses of plant roots to K + deprivation were studied in various species, including Arabidopsis (Arabidopsis thaliana; Armengaud et al, 2004), rice (Oryza sativa; Ma et al, 2012;Shankar et al, 2013), wheat (Ruan et al, 2015), and sugarcane (Saccharum officinarum; Zeng et al, 2015). However, in all these studies, K + was completely absent from the medium and the plants were analyzed after a relatively short period of time (1-2 weeks).…”
mentioning
confidence: 99%
“…Reports showed that potassium mainly participates in the electrical neutralization of inorganic and organic anions and macromolecules, pH homeostasis, the control of membrane electrical potential, the regulation of cell osmotic pressure, optimal protein synthesis, and photosynthesis [51]. In addition, as cofactors for many enzymes, K ions participate in many metabolic processes, such as nitrogen (N), sulfur (S), and phosphorus (P) assimilation, pyruvate synthesis, and sugar metabolism [52]. Potassium is taken up by the plant root through the epidermal and cortical cells, and then transported to the shoot and distributed to the leaves [53].…”
Section: Discussionmentioning
confidence: 99%
“…Due to recent advances that have increased genomic sequences with lots of plant species, low potassium stress transcriptome of several field crops and important economic plants have been studied, such as rice (Zhang et al, 2017;Ma et al, 2012), wheat (Ruan et al, 2015), barley (Zeng et al, 2014), watermelon (Fan et al, 2014), tobacco (Lu et al, 2015), sugarcane (Zeng et al, 2015) and pear (Shen et al, 2017). However, no such research on flax has yet been reported.…”
Section: Introductionmentioning
confidence: 99%